The Evaluation of Prophylactic Efficacy of Newly Developed Reversible Inhibitors of Acetylcholinesterase in Soman‐Poisoned Mice – A Comparison with Commonly Used Pyridostigmine. (6th June 2014) - Kassa, Jiri; Korabecny, Jan; Sepsova, Vendula; Tumova, Martina
Abstract The ability of four newly developed reversible inhibitors of acetylcholinesterase (PC‐37, PC‐48, JaKo 39, JaKo 40) and currently available carbamate pyridostigmine to increase the resistance of mice against soman and the efficacy of antidotal treatment of soman‐poisoned mice was evaluated and compared. No reversible inhibitor of acetylcholinesterase studied was able to decrease the LD50 value of soman in mice. Thus, the pharmacological pre‐treatment with pyridostigmine or newly synthesized inhibitors of acetylcholinesterase was not able to significantly protect mice against soman‐induced lethal acute toxicity. In addition, neither pyridostigmine nor new reversible inhibitors of acetylcholinesterase was able to increase the efficacy of antidotal treatment (the oxime HI‐6 in combination with atropine) of soman‐poisoned mice. These findings demonstrate that pharmacological pre‐treatment of soman‐poisoned mice with tested reversible inhibitors of acetylcholinesterase is not promising.